CIRCINATE BALANOPOSTHITIS AS A POSSIBLE CLINICAL MANIFESTATION OF GONOCOCCAL INFECTION - Pati Aji Achdiat; Rasmia Rowawi; Gynaecia Lamsu (Jurnal Kedokteran Syiah Kuala, 2018)
Abstract. Balanitis is defined as inflammation of the glans penis, while balanoposthitis is an inflammation of the glans penis and prepuce. Balanitis/balanoposthitis due to Neisseria gonorrhoeae (N. gonorrhoeae) is rarely reported. A case of balanoposthitis in a man clinically manifested as circinate balanoposthitis was reported to show the possibility of gonococcal infection manifested as circinate balanoposthitis. Bacterial examination with Gram staining and polymerase chain reaction (PCR) examinations from the lesions denoted the appearance of intracellular and extracellular Gram negative diplococcus bacteria and positive for Chlamydia trachomatis (C. trachomatis). Serological examination showed the reactive results for syphilis. The patient received oral medications of 400 mg cefixime single dose and 1-gram azithromycin single dose, also 2.4 million international unit (IU) intramuscular per week for 3 weeks. The gonococcal infection as the cause of balanoposthitis should be put in the differential diagnosis and any possible examination should be done to establish the most plausible etiology.Key words: balanitis, balanoposthitis, gonococcal balanoposthitis, circinate balanoposthitis